Flypaper Effect pada Belanja Daerah Kabupaten/Kota Provinsi Jawa Timur - Roro Indira Damayanti Juniartha; Siti Khoiriyah Maulid Nabila; Widya Ayu Pribandari; Windy Ulandari; Oryza Ardhiarisca (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study analyzes the influence of Local Own-Source Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) on regional expenditure in the regency and city governments of East Java Province, as well as examines the flypaper effect phenomenon. The results show that PAD, DAU, DAK, and DBH have a significant effect on regional expenditure, and the flypaper effect is found, where regional expenditure is more influenced by transfers from the central government than by PAD.